Particle Size and Surface Coverage Effects in the Stripping Voltammetry of Silver Nanoparticles: Theory and Experiment - Jones, S; Campbell, F; Baron, R; Xiao, L; Compton, R (2008)
Theory is presented for a mathematical model that includes two-dimensional diffusion for the stripping of randomly distributed metal nanoparticles. Theoretical results are compared with the reversible and irreversible limits in the approximate analytical form derived by Brainina and co-workers (Brainina, K. Z. Talanta 1971, 18, 513. Brainina, K. Z.; Lesunova, R. P. Zh. Anal. Khim. 1974, 29, 1302. Brainina, K. Z.; Vydrevich, M. B. J. Electroanal. Chem. 1981, 121, 1.) when considering an average coverage of material across the whole electrode surface instead of the individual particle environments considered in the presented theory. Experimental results are reported for the stripping of different-sized silver nanoparticles (AgNPs) from a basal-plane pyrolytic graphite electrode in 0.1 M NaClO4. Different loadings (as measured by the stripping charge) for each size of nanoparticle were investigated. The theory presented was used to explain the observed experimental trends in stripping peak potential and indicates that the Ag/Ag+ couple has electrochemically reversible kinetics. © 2008 American Chemical Society.